Chemical and Sensory Properties of Palopo (Local Soft Cheese) Produced Using Natural Additive as Milk Coagulant - Djoko Kisworo (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Palopo is a traditional food that originated in Taliwang, West Sumbawa. This traditional processed product is made of buffalo milk mixed with palm sugar and a natural coagulant of wild eggplant (Solanum carolinense). The purpose of this study was to determine the use of four natural coagulants such as Solanum carolinense; Caloutropis gigantea; Wrigthia javanica; and Averrhoa bilimbi L. as milk coagulant on the quality of soft cheese (palopo). The study used a Completely Randomized Design (CRD), consisting of 4 treatments, Juice of four natural coagulants in 2.5 %, and repeated 5 times. The data obtained were analyzed using ANOVA (Analysis of Variance) at a 5 % level using Statistical Analysis System (SAS) Software and continued tested using Least Significant Difference (LSD). The results showed that the addition of the treatments gave a significant effect on chemical and organoleptic quality. It was concluded that the treatment of CG (Caloutropis gigantea) was the best in terms of the chemical content and organoleptic value. The overall panelists' acceptability of the palopo were the CG (Caloutropis gigantea) treatment, Moreover, the most preferred palopo' taste ranged from CG, SI, and WJ respectively, with the brownish-yellow color, slightly milky aroma, slightly chewy texture, sweet taste so that the panelists liked it.